Microstructured BN Composites with Internally Designed High Thermal Conductivity Paths for 3D Electronic Packaging. Issue 38 (23rd August 2022) - He, Hongying; Peng, Weixiang; Liu, Junbo; Chan, Xin Ying; Liu, Shike; Lu, Li; Le Ferrand, Hortense
Abstract: Miniaturized and high‐power‐density 3D electronic devices pose new challenges on thermal management. Indeed, prompt heat dissipation in electrically insulating packaging is currently limited by the thermal conductivity achieved by thermal interface materials (TIMs) and by their capability to direct the heat toward heat sinks. Here, high thermal conductivity boron nitride (BN)‐based composites that are able to conduct heat intentionally toward specific areas by locally orienting magnetically functionalized BN microplatelets are created using magnetically assisted slip casting. The obtained thermal conductivity along the direction of alignment is unusually high, up to 12.1 W m −1 K −1, thanks to the high concentration of 62.6 vol% of BN in the composite, the low concentration in polymeric binder, and the high degree of alignment. The BN composites have a low density of 1.3 g cm −3, a high stiffness of 442.3 MPa, and are electrically insulating. Uniquely, the approach is demonstrated with proof‐of‐concept composites having locally graded orientations of BN microplatelets to direct the heat away from two vertically stacked heat sources. Rationally designing the microstructure of TIMs to direct heat strategically provides a promising solution for efficient thermal management in 3D integrated electronics. Abstract : Using the magnetically assisted slip casting method, microstructures of boron nitride composites are purposely designed and highly oriented to achieve unusually high thermal conductivity and directional heat transfer toward specific areas along the direction of microplatelet alignment, opening up the solutions for the next‐generation thermal management for 3D electronic packaging.